PROBLEM-2014 AND CENTRAL ASIAN SECURITY - SYROEZHKIN, Konstantin (CENTRAL ASIA AND THE CAUCASUS, 2013)
The author analyzes the outcome of the 12 years of the counterterrorist operation in Afghanistan and the problems it has created. He looks at some of the political aspects related to the 2014 pullout and the main threats and challenges to regional security emanating from Afghanistan. The external threats to regional security, their potential exacerbation because of the coalition withdrawal, and their potential localization are likewise analyzed. He also examines the SCO’s possible involvement in settling the Afghan problem and the fields and spheres in which this organization could apply its potential.